Receiving hospital characteristics associated with survival after out-of-hospital cardiac arrest - Callaway, Clifton W.; Schmicker, Robert; Kampmeyer, Mitch; Powell, Judy; Rea, Tom D.; Daya, Mohamud R.; Aufderheide, Thomas P.; Davis, Daniel P.; Rittenberger, Jon C.; Idris, Ahamed H.; Nichol, Graham (Resuscitation, 2010)
Survival after out-of-hospital cardiac arrest (OOHCA) varies between regions, but the contribution of different factors to this variability is unknown. This study examined whether survival to hospital discharge was related to receiving hospital characteristics, including bed number, capability of performing cardiac catheterization and hospital volume of OOHCA cases. Prospective observational database of non-traumatic OOHCA assessed by emergency medical services was created in 8 US and 2 Canadian sites from December 1, 2005 to July 1, 2007. Subjects received hospital care after OOHCA, defined as either (1) arriving at hospital with pulses, or (2) arriving at hospital without pulses, but discharged or died ≥1 day later. A total of 4087 OOHCA subjects were treated at 254 hospitals, and 32% survived to hospital discharge. A majority of subjects (68%) were treated at 116 (46%) hospitals capable of cardiac catheterization. Unadjusted survival to discharge was greater in hospitals performing cardiac catheterization (34% vs. 27%, p = 0.001), and in hospitals that received ≥40 patients/year compared to those that received <40 (37% vs. 30%, p = 0.01). Survival was not associated with hospital bed number, teaching status or trauma center designation. Length of stay (LOS) for surviving subjects was shorter at hospitals performing cardiac catheterization ( p < 0.01). After adjusting for all variables, there were no independent associations between survival or LOS and hospital characteristics. Some subsets of hospitals displayed higher survival and shorter LOS for OOHCA subjects but there was no independent association between hospital characteristics and outcome.